The Double Burden of Malnutrition in Indonesia - World Bank (Jakarta, 2014)
The purpose of this report is to assess the double burden of malnutrition (DBM) problem in Indonesia. It builds on to the Indonesia landscape analysis country assessment (LACA) report, which found that overweight and underweight co-existed among young children, confirming that the DBM is already a concern in Indonesia. The focus of the LACA was on maternal and child under nutrition and especially on the extent of scaling-up of an essential package of interventions for improving maternal and child under nutrition. The focus of this report is on over nutrition, it also looks at how under nutrition contributes to this problem across the life course, including the links to the non-communicable diseases (NCDs), and especially those that are diet-related such as diabetes, hypertension, dyslipidaemia , and cardiovascular disease (CVD). The assessment is based on information collected during a visit to Jakarta and Yogyakarta in late November 2011 when interviews were held with the key actors involved in DBM problems in Indonesia. The report describes what the DBM means as well as what its consequences are, examines the DBM situation in Indonesia, and makes recommendations on what actions should be taken to both prevent and mitigate problems across the life course.